Are African Current Account Deficits Different? : Stylized Facts, Transitory Shocks, and Decomposition Analysis - Zanforlin, Luisa (IMF Working Papers; Working Paper ;, 2001)
This paper analyzes the behavior of current account deficits in Africa and estimates whether the deficits are excessive with respect to fundamentals. The findings are the deficits are (i) not very persistent; (ii) positively linked with domestic growth; (iii) strongly linked with public (and private) savings, suggesting that fiscal consolidation in IMF-supported programs may be relatively effective; (iv) linked with aid flows, so as to close the external gap, and (v) linked with currency depreciation and the terms of trade. The deficit is "excessive," as it is almost 3 percent of the gross national disposable income above the equilibrium level.